1980
DOI: 10.1038/icb.1980.9
|View full text |Cite
|
Sign up to set email alerts
|

Arboviruses of Coastal South‐eastern Australia

Abstract: Summary During investigations of epidemic polyarthritis at Nelson Bay, New South Wales, 12 strains of Ross River virus, the causative agent, were recovered from pools of mosquitoes. In addition, the mosquito pools yielded 9 strains of the flavivirus Edge Hill, 4 strains of a bunyavirus, Gan Gan, 1 strain of an orbivirus Tilligerry, and 1 strain of an ungrouped probable arbovirus, Yacaaba. The latter 3 viruses were found to be antigenically distinct from previously recorded arboviruses. A case of epidemic polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…It does not cross-react strongly in serological assays with other EUBV isolates and it is not closely related to EUBV by hybridrization [19], [41], [42], leading to suggestions that the current classification of PATAV should be re-examined [19], [42], [43]. PATAV does show low level cross-reactivity in complement fixation (CF) tests with BTV and EHDV serogroups [19], [43] and it has been suggested that it could be reclassified as an EHDV [19], [43].…”
Section: Discussionmentioning
confidence: 99%
“…It does not cross-react strongly in serological assays with other EUBV isolates and it is not closely related to EUBV by hybridrization [19], [41], [42], leading to suggestions that the current classification of PATAV should be re-examined [19], [42], [43]. PATAV does show low level cross-reactivity in complement fixation (CF) tests with BTV and EHDV serogroups [19], [43] and it has been suggested that it could be reclassified as an EHDV [19], [43].…”
Section: Discussionmentioning
confidence: 99%
“…Ross River (RR) virus activity along the south coast of New South Wales has been previously reported (Cloonan et al, 1982a;Cloonan et al, 1982b) and the virus has been isolated from mosquitoes collected in south coast forests both in 1972 (Marshall, Woodroofe and Gard, 1980) and in 1982 (Cloonan et a!., 1982b). Other arboviruses recovered from mosquitoes collected in the same area include Termeil (TER) virus , Trubanaman (TRU) virus (Vale et al, 1985), Barmah Forest (BF) virus which has been isolated from mosquitoes collected in the Batemans Bay area both in 1984 (Vale et al, 1985) and in 1985 from a pool of Aedes vigilax (Vale, McPhie and Cloonan, unpublished data), and Gan Gan (GG) virus which has been isolated from a pool of Culex spp.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, KUN has been obtained repeatedly from mosquitoes collected in the Murray Valley region of Victoria and N.S.W. (Marshall and Woodroofe, 1975), at Charleville in Queensland (Doherty et al, 1976) and in the Ord Valley of Western Australia (Liehne et al, 1981). KUN has also been isolated in Sarawak and Thailand.…”
Section: Introductionmentioning
confidence: 99%